PENGARUH PROGRAM SETEKSI MASUK TERHADAP PRESTASI BELAJAR SISWA SMU - Supriyoko Supriyoko (Universitas Negeri Yogyakarta, 2000)
The purpose of the research is to disclosure the influence of using entry seleition (NEM) ii 'physiial 'is'to program based on the original government examination score iuitor cindttion high school (SLTP), abstract reasoningability, and for senior high school SMU) students. The method used compute thi relationship of the entry selection program toward student achievement in Mathematics and English. The model of the research is a case study at the SMU Tamansiswa Bandung involving a data analysis ut d 1o, for the whole population of 454 students. The analysis technique this research is Product Moment Analysis and Linear Regression Analysis. From the data oulysis result it was concluded that entry seleition program has a positive and very significant effect achievembnt. Generally speaking it can be concluded that the entry selection program for for the student fuIU which consist of NEM SLTP, abstract reasoning'ability, and pttysical condition is very selection system ofthe new students.